How Does Unethical Behavior Spread? Gender Matters! - Kim L. Böhm; Sebastian J. Goerg; Lilia Wasserka-Zhurakhovska (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using an online experiment with two distinct dishonesty games, we analyze how dishonesty in men and women is influenced by either thinking or learning about the dishonesty of others in a related, but different situation. Thinking is induced by eliciting a belief about others' dishonesty in a different game. We find that such belief elicitation (1) increases males' (but not females') dishonesty and (2) has no influence on participants' beliefs about the dishonesty of others in the game that they themselves play. Learning is induced by receiving a signal about the actual honest or dishonest choices of others in a different game. We find that the level of unethical behavior provided in such a signal (1) increases females' (but not males') dishonesty and (2) is positively correlated with participants' beliefs about the dishonesty of others in the game that they themselves play. We conclude that gender matters when examining how unethical behavior spreads. Both genders update their beliefs about others' dishonesty in the same way when presented with information about others' choices, but dishonesty in men is triggered by merely thinking about others' dishonesty, while women only respond to actual information on others' dishonesty.
Keywords: C90; D01; D80; D91; 330; dishonesty; unethical behaviour; thinking and learning about other's dishonesty; gender; experiment